Communication Conflict Management Strategy of The Democratic Party - Dimas Andi Wiyono (PT ARRUS Intelektual Indonesia, 2025)
The essence of all activities carried out by humans in their daily lives shows that humans are social beings who communicate with one another. Communication patterns within each group or organization are crucial to unite the differences that exist in each individual, including characteristics, status, roles, and responsibilities within an institution or organization. Implementing communication within an organization is one way to prevent and address conflicts. The communication process in an organization will run smoothly if the conflict management follows the correct procedures. The theory used in this research is the conflict theory introduced by Max Weber, which states that the conflicting interests of individuals or groups are the most important determinants in the organization of social life. The aim of this research is to describe the communication conflicts in the case study of the Democratic political party organization, focusing on the role of its leader. The method used in this research is a literature review from various sources such as articles, journals, and books. The results of this study indicate that an organization will succeed in managing conflicts if it is guided by human resources (leaders) who possess several essential criteria, namely good communication patterns.